Delivery of care for functional gastrointestinal disorders: A systematic review. Issue 2 (3rd September 2019) - Basnayake, Chamara; Kamm, Michael A; Salzberg, Michael R; Wilson‐O'Brien, Amy; Stanley, Annalise; Thompson, Alexander J
Abstract: Background: A diverse range of treatments are available for the treatment of functional gastrointestinal disorders (FGIDs). Individual treatments, including drug therapies, behavioral therapy ("biofeedback"), psychological therapies, and dietary therapies, have been well validated in controlled, randomized trials and real‐life case series. However, few studies have evaluated models of delivery of care for the whole population of referred patients with an FGID. This review evaluates models of specialist outpatient care for the management of FGIDs. Methods: A systematic review was performed of full‐text articles published until October 2018 in Pubmed/Medline and Embase. Studies were included if they evaluated a model of outpatient care in a specialist setting for the treatment of adult patients with an FGID and included patient‐reported outcomes comprising symptoms, quality of life, or psychological well‐being. Results: Few studies have evaluated the delivery of care for the whole population of referred patients with an FGID, and there was one randomized comparison of different models of care. Two studies that evaluated the outcome of gastroenterologist‐only clinics suggested poor long‐term results. Two non‐comparative case series reported the outcome of multidisciplinary care, including gastroenterologists and psychological therapists, suggesting improved patient quality of life and psychological well‐being. Conclusions: Despite the high prevalence and cost of treating FGIDs, and the availability of effective treatments, there are few data and limited randomized comparisons reporting the outcome of different types of specialist care. The few data available suggest that multidisciplinary care is superior to gastroenterologist‐only care, but this needs to be validated in prospective comparative studies.